3-7 YOSHDAGI BOLALARGA AQLIY TARBIYA BERISHDA O‘YIN FAOLIYATIDAN FOYDALANISH - Qipchaqova Sevinchxon (PEDAGOGS, 2025)
Annotation: The article examines the role of mental education in the upbringing of preschoolers as full-fledged adults. The author emphasizes the importance of cognitive processes in the mental development of children. Thoughts on the effective use of game activities in mental education are covered